Association of Haptoglobin Phenotype With Neurological and Cognitive Outcomes in Patients With Subarachnoid Hemorrhage - Han, Sung Woo; Kim, Bong Jun; Kim, Tae Yeon; Lim, Seung Hyuk; Youn, Dong Hyuk; Hong, Eun Pyo; Rhim, Jong Kook; Park, Jeong Jin; Lee, Jae Jun; Cho, Yong Jun; Gaastra, Ben; Galea, Ian; et al. (Frontiers in Aging Neuroscience, 2022)
Background: To assess the association of haptoglobin (Hp) phenotype with neurological and cognitive outcomes in a large cohort of patients with subarachnoid hemorrhage (SAH). Methods: This prospective multicenter study enrolled patients with aneurysmal SAH between May 2015 and September 2020. The Hp phenotype was confirmed via western blots. The relative intensities of α1 in individuals carrying Hp2-1 were compared with those of albumin. Multivariable logistic and Cox proportional-hazards regression analyses were used to identify risk factors for six-month and long-term outcomes, respectively. Results: A total of 336 patients including the phenotypes Hp1-1 (n=31, 9.2%); Hp2-1 (n=126, 37.5%); and Hp2-2 (n= 179, 53.3%) were analyzed. Hp phenotype was closely associated with 6-month outcome (p=0.001) and cognitive function (p=0.013), and long-term outcome (p=0.002) and cognitive function (p<0.001). Compared with Hp1-1 as the reference value, Hp2-2 significantly increased the risk of 6-month poor outcome (OR=7.868, 95% CI: 1.764-35.093) and cognitive impairment (OR=8.056, 95% CI: 1.020-63.616), and long-term poor outcome (HR=5.802, 95% CI: 1.795-18.754) and cognitive impairment (HR=7.434, 95% CI: 2.264-24.409). Long-term cognitive impairment based on Hp phenotype was significantly higher in patients under 65 years of age (p<0.001) and female gender (p<0.001). A lower relative ɑ1 /albumin intensity (OR=0.010, 95% CI: 0.000-0.522) was associated with poor outcomes at 6 months, but not cognitive impairment in patients with SAH expressing Hp2-1. Conclusions: Hp2-2 increased the risk of poor neurological outcomes and cognitive impairment compared with Hp1-1. For Hp2-1, higher relative α1 intensities were related to 6-month favorable outcomes.